DINAMIKA PERKEMBANGAN PONDOK PESANTREN DI INDONESIA - Zulhimma, Zulhimma (IAIN Padangsidimpuan, 2013)
Islamic boarding school is an older Islamic educational institution in Indonesia. This plays very important to give education to people especially religion. At first, Islamic boarding school was a simple education institution with also simple management and only on religion subjects. At last, Islamic boarding school goes on subsystem of national education. Finally, it must follow the government system.